Health-related quality of life in children born preterm at school age: the mediating role of social support and maternal stress - Martínez-Shaw, Melissa Liher; Evensen, Kari Anne I.; Melero, Sandra; Sánchez-Sandoval, Yolanda (Frontiers in Psychology, 2024)
Research on health-related quality of life (HRQoL) of school-aged children born preterm (< 37 weeks of gestational age) is scarce and there are few studies examining the relationship with medical and family factors. The aims were to analyze HRQoL in a sample of 8-year-old children born preterm with very low birth weight (VLBW), to test a proposed theoretical model that examines the relationship with medical and socio-family factors, and to explore the mediation effects of maternal factors between perinatal variables, demographic characteristics and HRQoL. A total of 147 VLBW children and 116 mothers were assessed. The measures included for assessment were self-and parent-reported HRQoL, functional social support, maternal stress, socio-family risk index and neonatal medical risk index. Mediation analysis was applied to investigate mediation effects of the maternal factors. Mean self-and parent-reported KIDSCREEN scores were 55.1 (SD 10.1) and 58.2 (SD 9.1), respectively, indicating better HRQoL than the normed sample with a mean of 50 (p < 0.001). The total effect of the initial theoretical model was not significant, thus another partial model was validated. Socio-family risk index significantly influenced HRQoL (direct effect), and this relationship was mediated by functional social support and maternal stress (indirect effects). School-aged VLBW children and their parents reported better HRQoL than the mean reference value on KIDSCREEN-10 and -27. Maternal stress and social support had a mediating effect on the children’s HRQoL. These results could be used to tailor interventions in these families.